(untitled) - Marcovitz, Alan B. (Boston, 2008)
Introduction to Logic and Computer Design by Alan Marcovitz takes the successful formula realized in the author’s previous books and makes it even better. With the inclusion of several chapters on computer design, Marcovitz now offers everything a fundamentals-oriented logic design course might include. Further, this new book is supported by an ARIS site - McGraw-Hill's electronic homework management systems -- including 350 algorithmic problems and a host of new media supplements to make both the instructor’s and the student’s tasks easier. As with Marcovitz’s previous books, the clear presentation of concepts and well-paced writing style make Introduction to Logic and Computer Design the ideal companion to any first course in digital logic. Users rave about the book’s extensive set of examples — well integrated into the body of the text and included at the end of each chapter in sections of solved problems — that give students multiple opportunities to understand the topics being presented.
Keywords: Logic design,Nguyên lý thiết kế